Feasibility and effectiveness of a disease and care management model in the primary health care system for patients with heart failure and diabetes (Project Leonardo) - Marco Matteo Ciccone (Vascular Health and Risk Management, 2010)
Marco Matteo Ciccone1, Ambrogio Aquilino2, Francesca Cortese1, Pietro Scicchitano1, Marco Sassara1, Ernesto Mola3, Rodolfo Rollo4,Pasquale Caldarola5, Francesco Giorgino6, Vincenzo Pomo2, Francesco Bux21Section of Cardiovascular Disease, Department of Emergency and Organ Transplantation, School of Medicine, University of Bari, Bari, Italy; 2Agenzia Regionale Sanitaria – Regione Puglia (ARES), Apulia, Italy; 3ASL, Lecce, Italy; 4ASL, Brindisi, Italy; 5Cardiologia, Ospedale “Sarcone”, Terlizzi, Italy; 6Section of Endocrinology, Department of Emergency and Organ Transplantation, School of Medicine, University of Bari, Bari, ItalyPurpose: Project Leonardo represented a feasibility study to evaluate the impact of a disease and care management (D&CM) model and of the introduction of “care manager” nurses, trained in this specialized role, into the primary health care system. Patients and methods: Thirty care managers were placed into the offices of 83 general practitioners and family physicians in the Apulia Region of Italy with the purpose of creating a strong cooperative and collaborative “team” consisting of physicians, care managers, specialists, and patients. The central aim of the health team collaboration was to empower 1,160 patients living with cardiovascular disease (CVD), diabetes, heart failure, and/or at risk of cardiovascular disease (CVD risk) to take a more active role in their health. With the support of dedicated software for data collection and care management decision making, Project Leonardo implemented guidelines and recommendations for each condition aimed to improve patient health outcomes and promote appropriate resource utilization.Results: Results show that Leonardo was feasible and highly effective in increasing patient health knowledge, self-management skills, and readiness to make changes in health behaviors. Patient skill-building and ongoing monitoring by the health care team of diagnostic tests and services as well as treatment paths helped promote confidence and enhance safety of chronic patient management at home.Conclusion: Physicians, care managers, and patients showed unanimous agreement regarding the positive impact on patient health and self-management, and attributed the outcomes to the strong “partnership” between the care manager and the patient and the collaboration between the physician and the care manager. Future studies should consider the possibility of incorporating a patient empowerment model which considers the patient as the most important member of the health team and care managers as key health care collaborators able to enhance and support services to patients provided by physicians in the primary health care system.Keywords: partnerships, health team, patient empowerment, care coordination